Factors affecting the formation of public health in Ukraine (literature review) - Yakimenko, E. A.; Panov, B. V.; Mikhaylenko, V. L.; Gavrilenko, M. U. (Journal of Education, Health and Sport, 2018)
The health of the population is one of the greatest values of mankind and a necessary condition for the social and economic development of each country. To realize the potential of each person throughout life, it is necessary to create optimal conditions aimed at preserving health and ensuring a full life - the most important goals of the world community. These are the most important global goals that were reflected in the principles of the European policy "Health 2020: the foundations of European policy in support of the actions of the state and society for health and well-being".Healthcare is a complex of national and regional, interagency and intersectoral activities aimed at preventing the occurrence of diseases, preserving and strengthening human health.